Regulation of glucose transport in skeletal muscle during and after exercise - Kentaro Kawanaka (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Exercise is widely perceived to be an effective tool for prevention and treatment of type 2 diabetes, since reducing visceral fat accumulation by means of exercise protects against insulin resistance. However, not only reducing visceral fat but other mechanisms contribute to the benefits of exercise. The beneficial effects of exercise for prevention and treatment of type 2 diabetes is also partly due to muscle contraction-induced local adaptations, i.e. an insulin-independent increase in GLUT4-mediated glucose transport, increased insulin action of GLUT4-mediated glucose transport, and increased GLUT4 protein expression in skeletal muscles that actually performed exercise and used glycogen. These local adaptations cause rapid and fully glycogen repletion, leading to post-exercise glycogen supercompensation. This review deals with exercise/muscle contraction-related promotion of GLUT4-mediated glucose transport and GLUT4 protein expression, and especially focuses on the possible mechanisms behind the relationship between increased glucose transport and muscle glycogen repletion during the post-exercise period.